Clinical validation of a real-time applicator position monitoring system for gynecologic intracavitary brachytherapy. (27th July 2016) - Bou-Zeid, Wassim; Bauer, Christian; Kim, Yusung; Beichel, Reinhard R; Sun, Wenqing; Waldron, Timothy; Xia, Junyi
Abstract: Purpose: To validate the clinical feasibility and efficacy of a real-time applicator position monitoring system (RAPS) through a phantom study and a prospective clinical trial. Methods and materials: The RAPS measures the brachytherapy applicator displacement in real-time by computing the relative displacement between two infrared reflective targets, one attached to the applicator and the other to the patient's skin. A phantom study was performed to compare RAPS measurements with the ground truth. Six cervical cancer patients were enrolled in the clinical trial using MRI-based high-dose-rate brachytherapy with a Tandem-and-Ovoids applicator. The results from the RAPS are compared with the clinical method. Results: In the phantom study, an average difference between RAPS measurements and known displacements was 0.02 ± 0.01 mm in the superior-inferior direction, 0.02 ± 0.02 mm in the lateral direction, and 0.11 ± 0.06 mm in the anterior-posterior direction. In the clinical trial, the absolute difference in applicator displacement between the RAPS and the clinical method was 1.46 ± 1.13 mm. In all patient cases, a maximum applicator displacement of 6.66 mm (2.0 ± 1.5 mm) was observed using the RAPS. Conclusions: This work demonstrates the clinical efficacy of RAPS to measure applicator displacement.